Neural Correlates of Memory Decisions Made in the Face of Conflict - (:unkn) unknown (My University, 2018)
We’ve all experienced moments where, for some reason or another, we don’t want to reveal to others what we truly know. The current experiment investigated questions about the behavioral and neural correlates of these types of memory decisions made in the face of a conflicting goal. Participants in this experiment studied several scene-face pairs and were tested with three-face displays preceded by studied scene cues. They were instructed to indicate whether the three-face display contained the matching associate or not. Critically, half of the participants were instructed to simulate feigned memory impairment (i.e. simulators), while the remainder were instructed to perform optimally (i.e. controls). Eye movements and neural activity were recorded throughout this test. Consistent with the instructional manipulation, simulators performed worse than controls with their explicit responding. However, both groups showed comparable early viewing of the associate after the three-face display was presented. Analyses were conducted to identify the memory, attention, and cognitive control processes that contributed to these memory decisions while feigning memory impairment. Hippocampal activity during the scene cue predicted early viewing effects for simulators, even when they made incorrect responses. During the three-face display, hippocampal activity reflected memory accuracy among controls, but the opposite pattern was evident in simulator data. This pattern, with greater activity for incorrect than correct trials, was also seen for simulators in the anterior cingulate cortex, an outcome that likely reflects conflict between memory retrieval and decision making. Finally, group differences in parietal regions likely indicate greater reorienting of attention among simulators than controls. Together, these results suggest the recruitment of memory retrieval, attentional allocation, and cognitive control regions as individuals work to succeed at simulating memory impairment.
Keywords: Cognitive Control; Eye-Tracking; fMRI; Malingering; Memory